Dry eye disease in French elderly subjects: the Alienor Study. (7th June 2013) - Malet, Florence; Le Goff, Mélanie; Colin, Joseph; Schweitzer, Cédric; Delyfer, Marie‐Noëlle; Korobelnik, Jean‐François; Rougier, Marie‐Bénédicte; Radeau, Thierry; Dartigues, Jean‐François; Delcourt, Cécile
Abstract. Purpose: To describe dry eye disease in French elderly subjects. Methods: The Alienor Study is a population‐based study on age‐related eye disease in 963 residents of Bordeaux (France), aged 73 years or more. Self‐reported dry eye disease and use of artificial tears were documented through face‐to‐face interview. Dry eye symptoms were assessed using the Ocular Surface Disease Index (OSDI) questionnaire and tear film stability by tear break‐up time measurements (TBUT). Definite dry eye disease was defined as self‐reported dry eye, confirmed by use of artificial tears and/or OSDI greater or equal to 22. Results: Nine hundred and fifteen subjects, with mean age of 80 ± 4 years, returned the OSDI questionnaire. Of these, 271 (29.6%) subjects reported a dry eye disease and 135 (14.7%) were using artificial tears. An OSDI score > 22 was found in 359 (39.2%) subjects and a TBUT < 5 seconds in 335/746 (44.9%) subjects. Overall, definite dry eye affected 21.9% of subjects and was more frequent in women (27.1%) than in men (13.6%). After multivariate adjustment, dry eye disease was also significantly less frequent in subjects with high educational level (odds ratio (OR) = 0.49, 95% confidence interval (CI): 0.31–0.78 for long secondary school) and more frequent in subjects with ocular hypertension (OR = 1.61, 95% CI: 1.02–2.57) and those using anxiolytics (OR = 1.53, 95% CI: 1.02–2.29). Conclusions: This large observational study confirmed the high prevalence of dry eye symptoms among elderly subjects and confirmed some of the previously identified risk factors (in particular female gender and use of anxiolytics).